Satisfaction and quality of life of Palestinian women with newly diagnosed breast cancer: a one-year follow-up study - Titi, Ibtisam; El Sharif, Nuha (Frontiers in Psychology, 2025)
BackgroundBreast cancer significantly impacts women’s quality of life (QoL), particularly in low-resource settings like Palestine. Evaluating changes in QoL and satisfaction with care is essential to improve patient-centred oncology services.AimThis study aimed to assess satisfaction with care and quality of life (QoL) among newly diagnosed women with breast cancer in the southern West Bank, Palestine.MethodsA prospective follow-up study included 144 newly diagnosed women with breast cancer treated at governmental hospitals in the southern West Bank. Quality of life was assessed at diagnosis and one year later using the Arabic versions of the EORTC QLQ-C30 and QLQ-BR23, while satisfaction with care was measured by the EORTC IN-PATSAT32. Descriptive statistics, bivariate analysis and multiple linear regression were performed to identify factors associated with QoL after treatment.ResultsThe mean global health score (QLQ-C30) was 45.78, with functional and symptom scores of 43.17 and 37.19 (QLQ-BR23), respectively. Age was positively associated with body image (B = 22.61, 95% CI: 14.6–30.5) but negatively linked to sexual functioning (B = −14.44, 95% CI: −20.4-8.4), sexual enjoyment (B = −13.66, 95% CI: −21.1-6.1), and increased systemic side effects (B = 12.57, 95% CI: 6.8–18.3). Marital status improved sexual functioning (B = 33.89, 95% CI: 25.2–42.5) and enjoyment (B = 26.50, 95% CI: 15.5–37.4). Satisfaction with healthcare providers was associated with better body image (B = 0.34, 95% CI: 0.2–0.4) and sexual functioning (B = 0.19, 95% CI: 0.01–0.3). Clean, comfortable services and skilled nurses were linked to fewer therapy side effects (B = −0.24, 95% CI: −0.3-0.1) and less distress from symptoms like hair loss (B = −0.19, 95% CI: −0.35-0.0). However, Access to services was positively associated with systemic therapy side effects (B = 0.25, 95% CI: 0.01–0.4).ConclusionThis study demonstrated significant changes in QoL and satisfaction with care among newly diagnosed Palestinian women with breast cancer, notably exacerbated by the challenges of a country in conflict. Improving patient-centered care is essential for enhancing patient experience and treatment outcomes in Palestine’s resource-limited and frequently unstable healthcare context. Healthcare services should emphasize efficient symptom management, open communication, and enhanced psychosocial support networks for cancer patients, acknowledging the unique stressors and limited infrastructure characteristic of a conflict-affected area.